Civilization Policy of the Mission of the Catholic Church in Malang, Indonesia During Dutch Colonialism: a Historical Analysis - Tinambunan, Edison Robertus Lamarsen (Mission studies, 2025)
The Catholic church started in Malang, Indonesia before and during colonialism. This study focuses on discussing the civilization policy used by the church during Dutch colonialism. A descriptive qualitative research method was applied to analyse historical writings and archives from relevant institutions. The results showed the emergence of Christianity, especially the Catholic church, through the Portuguese mission. This was continued by the arrival of the Jesuit congregation in East Java during the Dutch colonial era. The Propaganda Fide policy implemented was observed to have changed the strategy of the Catholic church by dividing the two service areas in East Java; the Carmelite Order was responsible for the Eastern part of East Java. This study showed that the effectiveness of the church’s civilization policy designed to advance the mindset and attitude of the people in Malang, Indonesia was responsible for its sustenance and not Christianization.